1982
DOI: 10.1161/01.cir.66.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Studies of platelet factor 4 and beta thromboglobulin release during exercise: lack of relationship to myocardial ischemia.

Abstract: SUMMARY Platelet activation, which results in release of the platelet-specific proteins platelet factor 4 (PF4) and BTG thromboglobulin (BTG), may participate in exercise-induced myocardial ischemia by the formation of intravascular platelet aggregates or the generation of vasoactive substances such as thromboxane A2. We sought to determine if platelet release occurs during exercise-induced ntyocardial ischemia and its relationship to exercise-induced catecholamine release in 10 normal males (mean age 29 + 6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

1983
1983
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 32 publications
2
17
2
Order By: Relevance
“…The second explanation is supported by the results of 8traton et al [32], who found a correlation between adrenaline increase during exercise and both platelet factor 4 and fl-thromboglobulin levels. These authors did not observe any relation between these alterations and pain in patients with ischemic heart disease.…”
Section: Discussionmentioning
confidence: 76%
“…The second explanation is supported by the results of 8traton et al [32], who found a correlation between adrenaline increase during exercise and both platelet factor 4 and fl-thromboglobulin levels. These authors did not observe any relation between these alterations and pain in patients with ischemic heart disease.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, the phlebotomy procedure was ac companied by a transient elevation of the plasma concentrations of BTG and PF-4, a finding probably attributable to an in stant release of adrenaline. Therefore, as previously discussed by us and others, it is conceivable that patients suffering from chest pain and psychological stress unre lated to an underlying cardiovascular dis ease, in analogy with the situation in 'hy povolemic stress', would activate the adrenal-medullary system and thereby de monstrate increased platelet activation and secretion [4][5][6].…”
Section: Discussionmentioning
confidence: 88%
“…4,5]. It has further been suggested that platelet activation is in duced only provided the stress situation is accompanied by increased levels of circu lating adrenaline [6]. Loud noise is a com mon environmental stress factor [7][8][9], Noise stress is known to induce an acute increase in blood pressure, which is medi ated by the sympathetic nervous system [10].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, platelet activation measured by the secretion of platelet-specific proteins (PF4, ffI'G) or by the formation of thromboxane B2, may occur during exercise [37] and after emotional stress [8,38], which are known to increase the level ofcatecholamines in plasma. The specific inhibition by nicergoline of the activation of platelets by adrenaline in vitro and ex vivo and the reports that nicergoline inhibits platelet-mediated thrombosis in stenosed coronary arteries [11] and cortical arteries [39] in experimental animals in vivo could increase the potential therapeutic applications of nicergoline.…”
Section: Discussionmentioning
confidence: 99%